PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN PPKN - Bagunda, Putriana; Solong, Najamuddin Petta; Iskandar, Karmila (DIRASATUL IBTIDAIYAH, 2024)
AbstractThe aim of this research is to determine (1) the learning outcomes of class V students using the conversional model at Muhammadiyah Elementary School, North City, Gorontalo City (2) the learning outcomes of students using the Discovery learning model at Muhammadiyah Elementary School, North City, Gorontalo City (3) the effect of using the model. Discovery Learning on student learning outcomes in civics subjects at Muhammadiyah Elementary School, North City, Gorontalo City. This thesis uses quantitative experimental research. This research was conducted at Muhammadiyah Elementary School, North City, Gorontalo City. The sample in the research consisted of 2 classes, namely the experimental class and the control class, totaling 40 students. This data collection uses pre-test and post-test multiple choice questions. The data analysis techniques used are normality test, homogeneity test, and t-test. The findings in this research are: that the post-test results obtained by class VA as an experimental class with an average value of 93.33 and class VB as a control class with an average value of 68.44. Calculation of the t-test in post-tets tcount (-11.784) ttable (1.685) which means there is a difference in the average of the control class and the experimental class. Which means the work (Ha) in this research was accepted while (Ho) was rejected. In this way, researchers can conclude that there is an influence on the application of the Discovery Learning learning model on student learning outcomes in Civics subjects at Muhammadiyah Elementary School, North City, Gorontalo City. Keywords: Pengaruh Model Discovery Leaarning; Hasil Belajar Siswa.